South African Government Functionality Assessment through the Eyes of Ordinary Citizens - (:unkn) unknown (My University, 2024)
While there are promises of improving in areas such as creation of jobs, law enforcement, education and other fields by government representatives, it seems as if the targeted beneficiaries or citizens no longer believe in government interventions. They see the government deteriorating in general service delivery and many believe the government functionality in providing safety and better life to all citizens is compromised and in downward trajectory as this is even widely reported by South African media. This qualitative study was intended to stipulate different works done by different government departments and agencies and use the beneficiaries accessible for participation to share their views in service delivery as received from specific agencies. In simple terms, this study focusses on understanding how ordinary citizens rate government delivery in general and how this is depicted by the media sources. In majority, the study is based on desk top data with limited observation and some face-to-face interviews. The study revealed that indeed there are levels of dissatisfaction from members of the community, and some believe the functionality of the government of South Africa is questionable. Some even compare the first ten years of the democratic South Africa ending up in 2004 to the rest and argue that things are going to worse situations in South Africa as they feel no longer protected and no longer gearing to the creation of better life. There are citizens who believe South Africa has become kakistocracy state as it seems unable to come with effective plans in many areas of service delivery. On the other hand, this provides media with multiple negative headlines.
Keywords: African Research